A PROPOSED EDUCATIONAL PROGRAM BASED ON THE PROBLEM-SOLVING STRATE.GY FOR TEACHING BASIC VOLLEYBALL SKILLS TO INTERMEDIATE SCHOOL STUDENTS - Esraa Abdulzahr Irkhayyis; Ali Abdulkarem Abdulhussein; Rasul Raad Qasim; Munadhil Adil Kasim (Proximus Journal Publishing, 2025)
The present study aims to identify the effect of the problem-solving strategy on learning the accuracy of serving, spiking, and blocking in volleyball. The researcher adopted the experimental method, and the study sample consisted of 40 male students in the first semester of the academic year 2023–2024. The sample was equally divided into two groups: an experimental group taught according to the problem-solving model, and a control group taught using the traditional model. The results of the study indicate that both the experimental and control groups showed improvement in learning the targeted skills, but to varying degrees. The experimental group outperformed the control group as a result of using the problem-solving strategy, in comparison with the control group, which relied on the traditional method (demonstration). Accordingly, it is recommended that further research and studies be conducted to examine the impact of the problem-solving strategy on developing skill-related aspects in games and other sport fields. It is also suggested to investigate the effect of this strategy on discovering and developing students' creative abilities while learning various skills.
Keywords: Educational Program; Strategy; Problem-Solving; Basic Skills